Sustainable valorization of corncob biochar as a slow-release fertilizer - Suryansyah Surahman; Andriyana Gustam; Gilang Bayu Prawira; Andi Magfiranur (Anjoro: International Journal of Agriculture and Business, 2026)
This study aimed to evaluate the effect of corn cob biochar as a slow-release organic fertilizer on the growth and yield of maize plants and to determine its optimal dosage for achieving this effect. The study used five biochar dosage treatments: 0, 5, 10, 15, and 20 t.ha–1, with three replicates each. The results showed that the application of biochar significantly affected the plant height, leaf number, and stem diameter. The highest dosage (20 tons.ha–1) produced the best values for these parameters. In terms of yield components, biochar had a significant effect on the weight of fresh-peeled cobs, whereas the number of cobs and cob length showed no significant differences among the treatments. Overall, a dose of 20 tons.ha–1 was recommended as the optimum dose under the conditions of this experiment. These findings confirm the potential of corn cob biochar as a sustainable organic fertilizer that can increase maize productivity through gradual nutrient release mechanisms.